The Role of The Digital Economy in The Development Of The Human Capital Market - Abdurakhmanova, Gulnora; Irmatova, Aziza; Shayusupova, Nargiza; Rustamov, Dostonbek (International Journal of Psychosocial Rehabilitation, 2020)
In the article, the concept of “the market of human capital” is considered as an integral part of the labor market and a determining factor in the innovative development of the economy. As the concept of “human capital” is clarified, such indicators as the human potential development index, the information and communication technologies development index, the global innovation index are analyzed. In order to develop an innovative economy, a model of managing the market of human capital was proposed.